A construção de conhecimento sobre música e decolonialidade no Brasil - Gómez Mejía, Carlos Mario (2023)
This work addresses the decolonial discussion in Brazil, in the area of music during the 21st century. In the first chapter I present a literature review on what I understand by decoloniality, to later delve deeper into the relationship between (de)coloniality and music (second and third chapters). In the fourth chapter, I present the results of a bibliographical survey that mapped 123 academic texts related to music, Brazil and decoloniality. The results point to: (1) an epistemological variety in the analyzed texts (which goes beyond the contributions of the Modernity/Coloniality group); (2) a relationship between academic production on decoloniality and approaches to popular music; (3) a significant part of the analyses presented in these works was limited to the lyrics of the song, leaving aside sound-related aspects; (4) the abundance of works in the field challenges one of the most common criticisms within decolonial works, namely, that of a lack of ethnographic analyses based on the field and with specific guidelines (RESTREPO and ROJAS, 2010); (5) Within the thematic areas covered we find musical education, decolonial feminism, Indigenous music, Afro-diasporic music, an approach from the human sciences and ethnomusicology, as well as from contemporary and/or experimental music; (6) there is a dialogue with other countries and regions in the production of knowledge (in terms of research themes and authors), showing that the decolonial discussion in Brazil is not closed in on itself; (7) we found multiple texts (especially within musical education) that diagnose the problem of coloniality and propose paths, however, attempts to implement specific changes are still at an early stage. Starting from the idea that decoloniality is not a metaphor and must be accompanied by actions (TUCK and YANG, 2012), in chapter five I present a discussion (based on bibliographic and documentary research) of the work developed within the Amazon Center for Music Research (NAP) by myself and other researchers. The objective of this chapter is to develop a conceptual framework for decolonial ubimus.